Fiscal Stress in Kerala? Beyond Off-budget and Contingent Liabilities - George, Justine; Sasidharan, Nandu (Economic and Political Weekly, 2025)
Kerala has been experiencing fiscal stress of varying intensities since the 1980s, mainly brought about by the structure of public expenditure (Mohan and Shyjan 2007), inadequate public resource mobilisation (Sebastian 2019), and the state government's in
Keywords: Contingent Liabilities; Kerala; Off-budget; Fiscal Stress